Implementasi Konsep Reward dan Punishment dalam Meningkatkan Interaksi Edukatif dalam Kegiatan Pembelajaran: Implementation of the Concept of Reward and Punishment in Increasing Educational Interaction in Learning Activities - Muzammil, Muzammil (PUSAT PUBLIKASI ILMIAH SEKOLAH TINGGI AGAMA ISLAM (STAI) AL-YASINI PASURUAN, 2023)
Reward and punishment as part of learning tools have a very important role in increasing the effectiveness of learning because at least one of the real impacts that will be seen in giving this reward and punishment is the emergence of motivation, discipline and an increase in student interest and enthusiasm for the implementation of educational and learning activities. This study aims to determine the Implementation of the Concept of Reward and Punishment in Increasing Educational Interaction in Learning Activities, using a qualitative approach and with the type of case study research. The results obtained in this study show that with the rewards and punishments given in accordance with the correct rules, principles and procedures, it has a very good impact on increasing educational interactions in learning activities. The educational interaction in question is the creation of a learning atmosphere that supports the development of talents, interests and potentials. The form of attitude seen as the impact caused by the implementation of rewards and punishments in this study is the high motivation of students to continue to improve themselves and improve their achievements, as well as being motivated to obey the rules and regulations that apply as specific implications of punishment for students who have low levels of discipline and compliance. The form of reward and punishment given in response to students' positive and negatic attitudes is by giving praise, support, respect, gifts and awards, while the forms of punishment applied are in the form of notices, reprimands, warnings, and punishments The results showed that the level of the village government apparatus capacity in carrying out village government administration in Pekon Gunung Sugih, Balik Bukit District, West Lampung Regency was in the high category. Based on the calculation of the interval obtained from the answers of each respondent to the questionnaire given, the ability of village government officials to carry out village government administration in Pekon Gunung Sugih, Balik Bukit sub-district, West Lampung Regency is 60%, meaning that the level of ability to carry out orderly administration of village government officials in Pekon Gunung Sugih, Balik Bukit District, West Lampung Regency is quite good. From the results of research in the field and in order to improve orderly village government administration, there are still village officials or respondents who have not implemented an orderly village government administration. For this reason, in order to achieve successful development and an orderly village administration administration, the parties concerned are expected to immediately carry out improvements and socialization related to administrative activities in the village.